An Updated Systematic Review Of Skin Grafts In Urethral Stricture Disease - Tuweno, Erdiansjah Taher; Gahari, Wira Amaz (Poltekkes Kemenkes Tasikmalaya, 2024)
The urethra in men has a dual function, namely as a pathway for urine and a pathway for semen from the reproductive organs.The purpose of this literature review is to find out some appropriate treatments for the problem of Urethral Stricture disease.This research method uses descriptive qualitative with a systematic literature review (SLR) approach. It is a type of article review that aims to find evidence of clinical efficacy (evidence-based) of a problem, so that a problem-solving suggestion is obtained. The results of the literature found include; The urethroplasty technique is considered a minimally invasive surgical technique and is more efficient than urethrotomy and the type of graft, oral mucosa and gelniltal mucosa have become the gold standard matelrilal substiltutel for relocation of urethral structures, although there has been rapid progress in the development of urethral grafts. The reconstructive urologist should be familiar with the different types of assistive devices to ensure that the selected assistive device is suitable for the needs caused by siltation.